The Pedagogical Value of Group Work as an Alternative in Instruction in The Moroccan EFL First-Year Baccalaureate Grammar Classes - Omarakly, Elmostafa (Universitas Jambi, Magister Program of English Education Department, 2025)
This study aimed to examine the pedagogical value of group work in grammar classes. To this end, the study adopted three major interrelated criteria: grammar self-concept, grammar engagement, and grammar achievement. Methodologically, the study used a quasi-experimental design. Two intact groups of 72 students were randomly assigned to control and experimental groups. The experimental group benefited from group work activities while the control group relied on traditional whole-class instruction. The study used three research instruments: a Grammar Self-concept scale, a Grammar Engagement Scale, and a Grammar Achievement Test. The Independent Samples t-test results revealed statistically significant differences in favour of the experimental group in all three investigated variables. Additionally, the results showed that the experimental group marked a statistically significant improvement between the pre- and post-stages of the study in all three areas, which was not the case for the control group, particularly at the grammar self-concept and engagement levels.